A Model for Ethical Decision Making in Business: Reasoning, Intuition, and Rational Moral Principles - Woiceshyn, Jaana (2011)
How do business leaders make ethical decisions? Given the significant and wide-spread impact of business people’s decisions on multiple constituents (e.g., customers, employees, shareholders, competitors, and suppliers), how they make decisions matters. Unethical decisions harm the decision makers themselves as well as others, whereas ethical decisions have the opposite effect. Based on data from a study on strategic decision making by 16 effective chief executive officers (and three not-so-effective ones as contrast), I propose a model for ethical decision making in business in which reasoning (conscious processing) and intuition (subconscious processing) interact through forming, recalling, and applying moral principles necessary for long-term success in business. Following the CEOs in the study, I employ a relatively new theory, rational egoism, as the substantive content of the model and argue it to be consistent with the requirements of long-term business success. Besides explaining the processes of forming and applying principles (integration by essentials and spiraling), I briefly describe rational egoism and illustrate the model with a contemporary moral dilemma of downsizing. I conclude with implications for further research and ethical decision making in business.
Keywords: Reason; rational egoism; Moral principles; Intuition; Integration by essentials; Ethical decision making